Aktivitas Penyimpangan Perilaku Remaja Di Lingkungan Seleksi Tilawatil Quran Bengkulu: Adolescent Behavior Deviation Activities in the Tiawatil Quran Bengkulu Selection Environment - Masruroh, Indah; Ummah, Putri Chaira; Osaren, Virenti Novika; Martilopa, Riski Martina; Dzulhijah, Doera Umi; Anggraini, Yola; Yani, Agri (Institut Agama Islam Sunan Giri Ponorogo, 2023)
Juvenile delinquency in the study of social problems can be categorized into deviant behavior. In the perspective of deviant behavior, social problems occur because there are deviations in behavior from various social rules or from prevailing social values and norms. Deviant behavior can be considered a source of problems because it can endanger the establishment of the social system. This study uses qualitative discriptive studies, namely research that examines a place that used to be the center of the crowd of very positive activities, namely the National Musabaqoh Tilawatil Quran (MTQ) activity, but is now a risky place to be misused by negative activities or activities of adolescents in the Tilawati Quran (STQ) Selection Mat. The purpose of this study was to determine the deviant activities of adolescent behavior in STQ, and the efforts of parents and preventive actions from surrounding community stores towards adolescents in the STQ Bengkulu environment using Qualitative Research methods. The results of the study found various behavioral deviations such as mugging, fornication, murder, drug transactions and wild racing.